P77 A Pharmacist delivered stratified conversion protocol from Hepatitis B Immunoglobulin (HBIG) to tenofovir or entecavir is efficacious, safe and cost-effective for prevention of recurrence of Hepatitis B virus (HBV) in Liver Transplant (LT) recipients. (6th September 2011) - Knighton, S; Agarwal, K; Heneghan, M; O'Grady, J; Bruce, M; Carey, I; Heaton, N; Suddle, A
Abstract : Introduction: The use of HBIG based prophylactic regimensto prevent recurrence of HBV in patients who have undergone LT is highly efficacious and well documented. However the long-term administration of HBIG can be time consuming, costly and inconvenient for the patient. With the advent of more potent oral anti-HBV agents the optimal long-term prophylactic strategy remains debatable. Aim: A prospective single centre experience of switching from an intra-muscular (IM) HBIG based regimen to monotherapy tenofovir (TDF) or entecavir (ETV) to prevent HBV recurrence post LT. Method: Patients receiving HBIG based prophylactic regimens were referred to a Pharmacist led clinic. Those with no serological evidence of HBV recurrence were considered for switch to monotherapy TDF or ETV. Decisions were based on clinical assessment and renal function, following an agreed stratified protocol. Data reported is an interim analysis 6 months post-switch. All results are presented as median. Results: Patients: To date 29 patients have been switched. The median time since switch is 9 months. 25 patients are >6 months post switch and included in the analysis. The median age was 61 (range: 28–81) years, 84% male, 60% Caucasian, 28% Black African and 12% Asian. At LT 6 were acute HBV with Liver failure, 7 had HCC and 4 had delta co-infection. At LT 22 had detectable HBV DNA, 11 were on lamivudine (LAM) and 1 was on LAM and adefovir (ADV). 52% patients had archived samples suitable for drug resistance testing. None had evidence of any drug resistant mutations. Results: Since LT all had received HBIG IM with HBsAb levels of 170 (range 101–454) mIU/ml. 80% were receiving concurrent LAM, 4% LAM and ADV and 16% no oral anti-HBV agent. The median time from LT to switch was 10 (range 2.6–20.3) years. At switch HBsAg and HBV DNA was undetectable in all subjects. 92% were on calcineurin inhibitor based immunosuppressive regimens. Serum creatinine was 104 (range 62–170) μmol/l, estimated glomerular filtration rate (eGFR) was 65 ml/min, 24 h urine creatinine clearance was 76 (range 41–150) ml/min and total protein excretion was 81 (range 31–441) mg/day. Serum ALT was 26 IU/l, phosphate was 0.98 mmol/l and vitamin D was 14 μg/l. 12 had hypertension and/or diabetes. 16 patients were switched to TDF, 9 patients with eGFR <60 ml/min or renal risk factors were switched to ETV. Six months after switch all patients remained HBsAg and HBV DNA undetectable and there was no difference in serum creatinine [103 (TDF 93, ETV 115) μmol/l], eGFR [65 (TDF 70, ETV 57) ml/min], ALT (23 IU/l), phosphate [1.03 (TDF 1.00, ETV 1.05) mmol/l] and vitamin D [17 (TDF 16.3, ETV 18.5) μg/l]. No therapy withdrawal/change was required due to adverse effects. The approximate drug cost saving made per patient/year from switching from HBIG to TDF or ETV is £11 000 and £10 000 respectively. Conclusion: A stratified conversion protocol, based on the assessment of virological parameters and renal co-morbidities, ensures patients can safely and effectively be switched from HBIG to TDF or ETV to prevent HBV recurrence post LT. HBsAg and HBV DNA remains undetectable and no deterioration in renal function has been observed to date. Significant drug cost savings can be achieved utilising this protocol.